Influence of family support in burden of caregivers of individuals with cerebrovascular accident sequelae - Kátia Lilian Sedrez Celich; Gabriela Maschio; Cláudio Claudino da Silva Filho; Tatiana Gaffuri da Silva; Silvia Silva de Souza (Universidad de Antioquia, 2016)
Objective. Understand the existence of a relation between the caregiver's overload of a stroke sequel patient and the family support. Methods. Quantitative/Qualitative research, described by six caregivers registered in the Basic Health Network in Chapecó/SC - Brazil. For (data) information gathering, the Burden Interview scale of Zarit Burden and a semi structured interview were used. The scale analysis was described with percentage while the interviews was based on the Minayo reference. Results. Four participants were identified with moderate overload, all of them focused only in the caregiving without any family support and. Two participants didn`t became overloaded, one had his familiar very independent and the other had family support, which can allow the caregiver to work, to have a better social life and to be financial stable. Conclusion. The familiar`s caregiver with family support feel more safe, reducing (easing) his load and being able to face the (care) daily challenges.   How to cite this article: Celich KLS, Maschio G, Silva Filho CC, Silva TG, Souza SS. Influence of family support in burden of caregivers of individuals with brain vascular accident sequelae. Invest. Educ. Enferm. 2016; 34(3): 544-550.